2016
DOI: 10.1007/s11130-016-0528-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Different Flavored Olive Oil Production Techniques: Healthy Value and Process Efficiency

Abstract: Three different flavoring methods of olive oil were tested employing two different herbs, thyme and oregano. The traditional method consist in the infusion of herbs into the oil. A second scarcely diffused method is based on the addition of herbs to the crushed olives before the malaxation step during the extraction process. The third innovative method is the implementation of the ultrasound before the olive paste malaxation. The objective of the study is to verify the effect of the treatments on the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 35 publications
3
76
0
Order By: Relevance
“…However, no clear trend could be established, an increase-decrease tendency being observed, depending on the olive oil quality, aromatic herb, and/or added concentration level. Nevertheless, Clodoveo et al (2016) did not found any differences using thyme or oregano. Gambacorta et al (2007) reported that PV and K 232 values decreased with the addition of the flavoring agents (rosemary, hot pepper, oregano, and garlic) although no significant effect was observed for FA and K 270 .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…However, no clear trend could be established, an increase-decrease tendency being observed, depending on the olive oil quality, aromatic herb, and/or added concentration level. Nevertheless, Clodoveo et al (2016) did not found any differences using thyme or oregano. Gambacorta et al (2007) reported that PV and K 232 values decreased with the addition of the flavoring agents (rosemary, hot pepper, oregano, and garlic) although no significant effect was observed for FA and K 270 .…”
Section: Resultsmentioning
confidence: 73%
“…Gambacorta et al (2007) reported that PV and K 232 values decreased with the addition of the flavoring agents (rosemary, hot pepper, oregano, and garlic) although no significant effect was observed for FA and K 270 . The different effects reported in the literature (increase or decrease trends) or the absence of a significant influence on olive oils quality parameter levels and their oxidation stability, after the addition of natural flavoring agents, may be tentatively explained considering: the differences in chemical composition and bioactive contents of the aromatic plants/herbs or species used, the use of fresh or dried natural flavoring agents, and consequently the incorporation of water in the system, the different flavoring techniques as well as the specific olive oil characteristics (Clodoveo et al, 2016). However, Khemakhem et al (2015) observed no changes between FA of flavored (sweet lime and sweet orange) and unflavored olive oils, although a significant increase of the PV values occurred for some flavored oils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A scarcely known innovative method is co-processing, based on the addition of herbs or other vegetable materials to the crushed olive paste before the malaxation step or during milling [63,68]; which may be implemented by the use of ultrasound before the olive paste malaxation [65]. In one of these studies, Cornicabra olives were co-processed under controlled conditions together with several fruits (apple, lemon and orange), spices (rosemary, thyme, basil and oregano) or leaves (rocket) in the Abencor laboratory system (Abengoa S.A., Seville, Spain) to obtain new VOO-based products [66,67,68].…”
Section: Optimization Of the Development Of Novel Functional Oilsmentioning
confidence: 99%
“…Moreover, when ultrasound was applied, the olive polyphenoloxidase—the endogenous enzyme responsible for olive oil phenol oxidation—was inhibited. As a consequence, antioxidant activity was significantly higher compared to the oils obtained by infusion [65]. Moreover, co-processing allows to produce oils ready to sell, instead the infused oils need to be filtered.…”
Section: Optimization Of the Development Of Novel Functional Oilsmentioning
confidence: 99%